The Women’s Rights in Divorce and Gender Equality Discourse in The Dynamics of Divorce in Madura - Maimun, Maimun (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This study investigates the dynamics of divorce in Madura and women's rights in divorce from a gender perspective. There are three main issues addressed in this study, those are the dynamics of divorce in Madura, women's rights in divorce, and gender equalities. This study is field research with a qualitative approach. The data used comes from primary data and secondary data. By conducting an in-depth analysis based on the sociological theory of gender, particularly Talcott Parson's theory of structural feminism, this study found some findings; firstly, the number of divorces, either from talaq divorce or judicial divorce, in Madura in the last five years has increased. This is because of the decline in ethics such as polygamy without the permission of the first wife, the low-income factor, the presence of a third party either due to parental interference or infidelity with other people, and disharmony due to disputes and differences of opinion; secondly, the number of divorce cases in Madura in the last five years has been dominated by judicial divorce rather than talaq divorce. In 2021, the percentage of judicial divorce compared to talaq divorce is around 73.04% to 26.96%, meanwhile, in 2020, this ratio was only 25.49% to 74.51%. Besides, in 2019, this was about 67.63% to 32.39%, in 2018 it reached 64.23% to 35.77%, and in 2017 it was about 67.18% to 2.82%; thirdly, the phenomenon of increasing divorce by law in Madura indicates that there has been a shift in perception among women about the meaning of divorce, as a response to the presence of legislation that provides room for legitimacy for women to file for divorce. In the perspective of contemporary feminism, the space for legitimacy contains the meaning of gender equality, and the patriarchal culture begins to collapse which has long been attached to the social system of the Madurese community.